Immediacy - Jason W. Alvis (PhaenEx: Journal of Existential and Phenomenological Theory and Culture, 2020)
At least for Schleiermacher, religion is life in immediate feeling. Whether or not we agree with him, immediacy can be understood as one essential aspect of feeling that makes feeling congenial as the means by which we tend to express the source of religious experience. Yet in general, immediacy is difficult to define and qualify. Is there a hope for immediacy in seeking “to be delivered from contingency” (Merleau-Ponty)? Is immediacy expressed in the instantaneity of how qualities of things are given in a “total interpenetration” (Sartre)? Or are “immediacy and mediation” always inseparable, thus leaving any “opposition between them to be a nullity”? (Hegel)?[i] Might immediacy entail a threat to faith through the absolutizing of the relative (Kierkegaard)? And finally, would not the absolute insistence upon mediation morph it into a new form of immediacy?